Bringing Community Based Participatory Research to Domestic Violence Scholarship: an Online Toolkit - Goodman, Lisa A.; Thomas, Kristie A.; Nnawulezi, Nkiru; Lippy, Carrie; Serrata, Josephine V.; Ghanbarpour, Susan; Sullivan, Cris; Bair-Merritt, Megan H. (Journal of family violence, 2018)
In the absence of ongoing involvement in the communities that are the subjects of research, even well-intentioned researchers can develop questions that are not relevant to community needs, employ methods that hurt community members, or disseminate findings in ways that are inaccessible to those most affected. Recognizing these harms, a growing number of domestic violence (DV) researchers have embraced community-based participatory research (CBPR), an approach in which researchers and community members share power at every level of the research process, co-creating knowledge that can be applied to enhance community well-being. Despite growing interest in this approach, however, there are insufficient opportunities for interested researchers to learn how to actually engage in it, especially in the DV context. To remedy this gap, the authors of this paper collaborated to develop an online toolkit for emerging researchers interested in CPBR. This brief report frames the need for CBPR in DV research using short vignettes that come from our own research experience; introduces Power Through Partnerships: A CBPR Toolkit for Domestic Violence Researchers ; and presents recommendations for developing, promoting, and disseminating future CBPR research. We chose to announce the development and availability of this toolkit in an academic journal in order to highlight its scholarly and practical relevance for researcher audiences who might be less familiar with the CBPR approach.